Understand the meaning and provisions for the administration of bookkeeping and tax records based on general provisions and tax procedures in Indonesia - M. Daffa Rajendra; Alysha Putri Rachman; Aura Yuliana W; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
Taxes are a mandatory contribution to the state. Where taxes are one of the state income. The purpose of writing this article is to provide information about taxation  in general and  get basic reasoning about the general procedures and provisions of taxation as a useful knowledge base for implementing tax law.  Writing is carried out using qualitative methods with sources obtained by means of literature studies. The result of this research is the existence of a system in tax collection, tax rates, principles, arising and elimination of tax debt, as well as obstacles to tax collection. So it is found that in taxation there is a collection system, as well as principles and rates that are adjusted to the tax subject and tax object. And there are obstacles in collecting taxes, as well as the causes of the emergence and elimination of taxes.